Strategi Kultural Muallim Syafi'i Hadzami: Merawat Nalar Islam Tradisional di Jantung Modernisasi Tanah Betawi - Muhammad Adi Yusuf; Moch Romli; Asep Rahmatullah (MUTAADDIB : Islamic Education Journal, 2026)
This paper explores how the prominent figure KH. Syafi'i Hadzami, affectionately known as Muallim Syafi'i Hadzami, successfully instilled classical Islamic teachings deeply within the Betawi community. The primary focus is on analyzing his unique educational approach, which ensured the continuous transmission of traditional scholarly knowledge across generations. The research relies purely on library research methodology, involving a careful analysis of various books, treatises, legal opinions (fatwas), and historical records written by and about the Muallim. This study dissects his unconventional teaching strategies practiced outside of formal classrooms, specifically within vibrant majelis taklim and halaqah (study circles). The secret to his success is revealed not merely through the robust classical curriculum (kitab kuning), but through his expertise in seamlessly integrating pure Islamic teachings with the everyday cultural nuances of Betawi society. This article demonstrates that traditional knowledge can thrive even amidst the pressures of urban modernization, provided it is delivered in a localized, community-embracing manner, as exemplified by Muallim Syafi'i Hadzami. Keywords: Islamic education, Betawi ulama, KH Syafii Hadzam